Sejarah Pemikiran Faith and Reason dalam Tradisi Reformed: dari Masa Abad Pertengahan hingga Masa Orthodoxy [A History of Thought on Faith and Reason in the Reformed Tradition: From the Middle Ages to the Period of Orthodoxy] - Eliata, Stephen Rehmalem (Universitas Pelita Harapan, 2022)
Research on historical thought of the Reformed tradition was started by Alexander Schweizer who proposed a method for reading history, namely centraldogmen. During its development, this method was received by a group of historians known as the Barthian tradition. In this tradition, the development of thought on the reformed tradition is considered to have been discontinued after John Calvin. These views surround the post-Calvinian theologians of the reformation tradition. Recent research tries to propose another method for reading history, namely by considering its continuity and discontinuity. With this new method, I intend to look at the history of the reformed tradition in the case of the relationship between faith and reason. This paper will discuss thoughts on the relationship between faith and reason from 3 different periods, that is the medieval period, the reformation period, and the orthodoxy period. From my analysis, I conclude that in the case of the relationship between faith and reason, there is a continuity of thought from the medieval period to the orthodoxy period. With this conclusion, the position of the Barthian tradition on reformed thinking needs to be re-evaluated.BAHASA INDONESIA ABSTRACT: Penelitian mengenai pemikiran sejarah tradisi reformasi dimulai oleh Alexander Schweizer yang mengajukan sebuah metode untuk membaca sejarah, yaitu centraldogmen. Dalam perkembangannya, metode ini diterima oleh sekelompok sejarawan yang dikenal dengan tradisi Barthian. Dalam tradisi ini, perkembangan pemikiran mengenai tradisi reformasi dianggap telah terhenti setelah John Calvin. Pandangan ini melingkupi para teolog tradisi reformasi pasca Calvin. Penelitian terbaru mencoba mengajukan metode lain dalam membaca sejarah, yaitu dengan mempertimbangkan kontinuitas dan diskontinuitasnya. Dengan metode baru ini, saya bermaksud untuk melihat sejarah tradisi Reformasi dalam hal hubungan antara iman dan akal budi. Tulisan ini akan membahas pemikiran-pemikiran mengenai relasi iman dan akal budi dari tiga periode yang berbeda, yaitu periode abad pertengahan, periode reformasi, dan periode ortodoksi. Dari hasil analisis saya, saya menyimpulkan bahwa dalam hal hubungan antara iman dan akal budi, terdapat kesinambungan pemikiran dari periode abad pertengahan hingga periode ortodoksi. Dengan kesimpulan ini, posisi tradisi Barthian dalam pemikiran reformasi perlu dievaluasi kembali.